2012
DOI: 10.4028/www.scientific.net/amm.226-228.1094
|View full text |Cite
|
Sign up to set email alerts
|

Deep Well of Coal Roadway Bolt-Cable Mechanism Analysis and its Engineering Application

Abstract: Cable Anchor Supporting mechanism theory analysis, combined with high geostress, composite roof and complex geological conditions, the deep well under conditions of coal roadway by small aperture, anchor on the form of the structure and high prestressed construction technology, engineering practice shows that the technology is simple and applicability,is deep well solve the high stress soft rock tunnel, large sections into bifurcation point supports of the effective way of the problem. Not only reduces the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…Practice has demonstrated that whether an anchor can provide sufficient pre-tightening force is key to realizing active support, effectively controlling the deformation of the surrounding rock in the roadway, and improving the anchor supporting quality in the deep roadway, especially in roadway support under broken rock mass conditions. Grouting anchor measures can effectively improve the integrity of the surrounding rocks in the roadway and effectively enhance the cohesion and internal friction angle of the surrounding rocks [1] [2] [3] [4], thereby increasing the selfsupporting ability of the surrounding rocks and significantly improving the roadway-supporting effect and quality. However, because the length of the free segment of the grouting anchor is usually quite short, the application of pre-tightening force is very limited [5] [6] [7], which fails to meet the demand of active support.…”
Section: Introductionmentioning
confidence: 99%
“…Practice has demonstrated that whether an anchor can provide sufficient pre-tightening force is key to realizing active support, effectively controlling the deformation of the surrounding rock in the roadway, and improving the anchor supporting quality in the deep roadway, especially in roadway support under broken rock mass conditions. Grouting anchor measures can effectively improve the integrity of the surrounding rocks in the roadway and effectively enhance the cohesion and internal friction angle of the surrounding rocks [1] [2] [3] [4], thereby increasing the selfsupporting ability of the surrounding rocks and significantly improving the roadway-supporting effect and quality. However, because the length of the free segment of the grouting anchor is usually quite short, the application of pre-tightening force is very limited [5] [6] [7], which fails to meet the demand of active support.…”
Section: Introductionmentioning
confidence: 99%